Paul and pseudepigraphy - Porter, Stanley E. (Pauline studies, 2013)
On Pauline pseudepigraphy: an introduction / Stanley E. Porter and Gregory P. Fewster -- 1. Critical issues in Pauline pseudepigraphy. Authorship and pseudepigraphy in early Christian literature: a translation of the most important source texts and an annotated bibliography / Armin D. Baum -- Pauline chronology and the question of pseudonymity of the Pastoral Epistles / Stanley E. Porter -- Hermeneutical issues in canonical pseudepigrapha: the head/body motif in the Pauline corpus as a test case / Gregory P. Fewster -- Style and pseudonymity in Pauline scholarship: a register based configuration / Andrew W. Pitts -- The problem of the Pastoral Epistles: an important hypothesis reconsidered / Jermo van Nes -- 2. Pauline pseudepigraphy within the Christian canon. A deutero-Pauline mystery?: ecclesiology in Colossians and Ephesians / Sigurd Grindheim -- The imitation hypothesis: pseudepigraphic remarks on 2 Thessalonians with help from documentary papyri / Christina M. Kreinecker -- Christology, Greco-Roman religious piety, and the pseudonymity of the pastoral letters / Linda L. Belleville -- Hebrews as an instructional appendix to Romans / Clare K. Rothschild -- The epistolory closing of Hebrews and Pauline imitation / Bryan R. Dyer -- 3. Pauline pseudepigraphy outside the Christian canon. Dusting off a pseudo-historical letter: re-thinking the epistolary aspects of the apocryphal Epistle to the Laodiceans / Philip L. Tite -- The pseudepigraphical correspondence between Seneca and Paul: a reassessment / Ilaria L.E. Ramelli -- The heretics' apostle and two Pauline pseudepigrapha from Nag Hammadi / Michael Kaler